Legal Issues of the Professional Skills of a Mediator - Mahmudov Nurmuhammad (Zien Journals, 2022)
The article deals with the preparation of mediators, the requirements for a mediator and professional skills. It is concluded that the list of mediators can include a capable person who has a higher professional education and work experience in a specialty that corresponds to the education received for at least two years, who has undergone special training and has received the qualification of a mediator.
Keywords: mediator; mediation; capable person; skills